An Overview on the Use of a Low Magnification Telescope in Low Vision - Woo, G.C (Canadian Journal of Optometry, 2021)
A Galilean telescope in its simplest form is a two element system consisting of a positive lens as an objective and a negative lens as an eyepiece. The system is restricted to lower magnifications and smaller fields of view in comparison with a Keplerian telescope. The image through the system, however, is always erect permitting its use for distance viewing for partially sighted patients. Other optical factors besides magnification and field of view that need to be considered include exit pupil size, focus adjustability, vertex distance, and image quality in terms of color and brightness. Such non optical factors as weight, portability, ease of use, appearance and cost are also influencing variables'. In this overview on the clinical use of low power telescopes in the examination room, only a few properties will be examined. The use of a low power full-field telescope in subjective and objective refractions will be discussed. Magnification through a telescope will also be elaborated upon.